Solving Hierarchical Constraints over Finite Domains with Local Search - Henz, Martin (Institutional Knowledge at Singapore Management University, 2004)
Many real world problems have requirements and constraints which conflict with each other. One approach for dealing with such over-constrained problems is with constraint hierarchies. In the constraint hierarchy framework, constraints are classified into ranks, and appropriate solutions are selected using a comparator which takes into account the constraints and their ranks. In this paper, we present a local search solution to solving hierarchical constraint problems over finite domains (HCPs). This is an extension of local search for over-constrained integer programs WSAT(OIP) to constraint hierarchies and general finite domain constraints.The motivation for this work arose from solving large airport gate allocation problems. We show how gate allocation problems can be formulated as HCPs using typical gate allocation constraints. Using the gate allocation benchmarks, we investigate how constraint heirarchy selection strategies and the problem formulation using two models: a 0–1 linear constraint hierarchy model and a nonlinear finite domain constraint hierarchy model.